Text formation at the English lesson using cooperative and productive methods - Fodor, Bálint (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The present contribution offers to illustrate the implementation of cooperative and productive learning methods in English as a Second Language (ESL) groups of any age, which possess no previous experience with the aforementioned routines. The presented introductory lesson is not only the fi rst step in acquiring a new learning method, but motivates the co-learning of the students as well. It also provides help for teachers to assess certain individual competence levels which might not be observed during regular lessons. I am giving an insight into the applied cooperative structures along with the discussion of the relevant literature, as I am also providing help to cope with problems and challenges to be encountered in the classroom. The included tasks and examples are ESL-specifi c, however they can easily be adapted to different subjects and group sizes. They may also serve as a guideline or inspiration for various classroom activities of different sorts.